Miejsce i funkcje planowania w działalności administracji: [Position and functions of planning in administration] (Studia Prawnicze / The Legal Studies, 1983)
The article ideals with planning as one of separate functions of the modern administration (both in capitalist and socialist states). The importance and meaning of the function has considerably increased lately (along with the increase of interference of the state into social life), nevertheless its principles, and in particular, regulation by law stifil arouses many doubts.After a short historical introduction, the author points to the immanently „technocratic" character of planing, which is connected with the fact that planning resolves itself into imperious government decisions (althought not in a direct legal sense), which aim at changing the existing state of affairs. Social consensus does not and cannot play an important role in the process in spite of permanent egalitarian and democratizing trends. Planning' is a result of a crisis (or a great number of them) and it would be unnecessary if there was plenty of everything for everybody. As a matter of fact, it is an unpopular and unwanted operation.A total approval or oven friendly attitude of the society towards it is, therefore, difficult to attain.Planning gives rise to many problems also in the light of law. A plan, as a form of the activity of the administration, belongs to the sphere between the law and administrative decision: it is niot indifferent from the legal point of view, bowever, it has not gained its own, evident identity yet. What is tmore, planning may be presumed to be used by the dininistratiion as a means of freeing itself from the rigours of positivistic legality in its strict meaning (there are many such means). As a matter of fact, activity through the plan consists, i. a., in its essential technical neutrality to laws because in case of a sudden change of economic, political and social situation, the plan may be easily changed or even rejected: however, if it assumed a strict legal form (e. ,g. a law) it would be more difficult. Neverthelmis, is such a situation legal supervision over the fulfilment of the plan, and also over its ,,legality" (e. g. supervision by the court) must be extremely limited, if not illusory. However, it is doubtful whether another solution could be proved correct: it would rather play a role of a smokescreen, blurring the real, in principle political, not a legal character of planning proceses.